Avaliação clínica do resultado da fixação artroscópica das lesões do labrum acetabular: coorte prospectiva - Carlos César Vassalo (2015)
Introduction: There is an increased interest regarding the acetabular labral injuries and especially in its forms of treatment. The labrum is essential for the stability and movement of the hip joint and helps preventing hip osteoarthritis. The fixation of labral lesions on the acetabular rim with anchors shows effectiveness with improvement in pain and function of the affected joint. Objective: to evaluate the clinical response of the arthroscopic fixation of acetabular labrum regarding the Harris Hip Score modified by Byrd. Patients and methods: we prospectively evaluated by the Harris Hip Score modified by Byrd (MHHS), 94 patients undergoing surgical hip arthroscopy for fixation of the acetabular labrum with metal or absorbable anchors with a minimum follow-up of 25 months. The patients were evaluated preoperatively, at 120 days and at the final evaluation, with the same score and only the patients who presented Tonnis grade 1 were included in the study. Results: 94 patients underwent the procedure, 50 in the left hip and 38 in the right hip, and six patients were operated on bilaterally; there were 56 male and 38 female patients with a mean age of 44.2 years (minimum of 23 years and maximum of 67 years). The median follow-up time was 44.5 months (minimum of 25 months and maximum of 76 months). The mean preoperative MHHS was 80.37 points, while the mean postoperative with 120 days was 94.13 points and at the final evaluation was 96.6 points. Four patients underwent total hip replacement and they had a low score HHSM preoperatively. Those patients were excludecd fro the final evaluation. Conclusion: The arthroscopic fixation of acetabular labrum proved to be effective, reproducible and safe, with good and excellent results in patients who did not have hip osteoarthritis at the time of treatment.